The Role of Language in Solving Mathematical Word Problems among Grade 9 Learners - Phaladi, Mabuse; Petrus, Rankhumise Mmushetji; Willy, Mwakapenda (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to explore mathematical word problem solving abilities among Grade 9 learners in Tshwane North District Schools. It highlighted how language plays a pivotal role in learning mathematics and understanding mathematical word problems. Moreover, it showed how language inadequecy and incorrect translation affect Grade 9 learners’ solutions to mathmatical word problems in schools around Tshwane North District. Methods: The study used both qualitative and quantitative methods. It also made use of contextual, exploratory, and descriptive statistical data. The study involved 26 nineth-grade learners in Tshwane North District secondary schools in Gauteng Province. Data collection was based on learners’ written work (a questionnaire) and analysing the results of the administered test. Data was analysed to detect the language difficulties that learners’ face when translating and solving mathematical word problems. The analysis process involved developing initial insights, coding, interpreting, and drawing conclusions to determine whether there is a connection between language proficiency and solving mathematical word problems. Results: The study showed that learners face difficulties in mathematical processes such as inadequate language comprehension when translating words into mathmatical symbols. It also revealed that there is a strong connection between vocabulary knowledge and word problem solving, resulting in learning challenges related to understanding the meaning associated with mathmatical word problems. Conclusions: Evidence from the word problem test for Grade 9 learners revealed that mathematical vocabulary and syntactic features are the main factors causing difficulties in understanding and solving mathmatical word problems.